Technology Spillover Effects and Policies: Evidence from Vietnam - NGO, Ngoc Minh (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020, 2020)
The paper examines empirical research on technology spillover effects from foreign invested enterprises (FIEs) to domestic manufacturing and processing firms in the North of Vietnam in 2016-2018 period. The Hausman test demonstrates Fixed Effects Model is suitable for the most-updated panel data. The empirical results indicate that FIEs create a pervasive effect on the productivity of domestic manufacturing and processing firms. However, the technology spillover effect depends on characteristics of domestic enterprise. Accordingly, the capitalization rate and production scale are positively correlated with technology spillover while the technology gap is negatively. This finding is useful for authorities to map out policies for domestic firms to absorb more effectively technology spillover effect from FIEs.